2021
DOI: 10.1126/sciadv.abf7282
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized and asynchronous modulation of seismicity by hydrological loading: A case study in Taiwan

Abstract: Delineation of physical factors that contribute to earthquake triggering is a challenging issue in seismology. We analyze hydrological modulation of seismicity in Taiwan using groundwater level data and GNSS time series. In western Taiwan, the seismicity rate reaches peak levels in February to April and drops to its lowest values in July to September, exhibiting a direct correlation with annual water unloading. The elastic hydrological load cycle may be the primary driving mechanism for the observed synchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 57 publications
1
33
1
Order By: Relevance
“…In a typical mainshock-aftershocks cluster, aftershocks are triggered by the mainshock, and hence are not considered as independent events. To avoid over-counting these clustered/dependent events, we decluster the MFT catalog, similar to the recent studies in Taiwan (Hsu et al, 2021;Steer et al, 2020). Specifically, we calculate the probability of background seismicity for each event above Mc in the MFT catalog using a stochastic declustering method (Zhuang, 2006;Zhuang et al, 2002Zhuang et al, , 2004 based on the epidemic-type aftershock sequence (ETAS) model (Table S3 in Supporting Information S1) (Ogata, 1988).…”
Section: Declustering the Seismicity Catalogmentioning
confidence: 99%
See 3 more Smart Citations
“…In a typical mainshock-aftershocks cluster, aftershocks are triggered by the mainshock, and hence are not considered as independent events. To avoid over-counting these clustered/dependent events, we decluster the MFT catalog, similar to the recent studies in Taiwan (Hsu et al, 2021;Steer et al, 2020). Specifically, we calculate the probability of background seismicity for each event above Mc in the MFT catalog using a stochastic declustering method (Zhuang, 2006;Zhuang et al, 2002Zhuang et al, , 2004 based on the epidemic-type aftershock sequence (ETAS) model (Table S3 in Supporting Information S1) (Ogata, 1988).…”
Section: Declustering the Seismicity Catalogmentioning
confidence: 99%
“…Steer et al (2020) attributed this to the crustal unloading caused by the intense and prolonged sediment erosion after typhoon Morakot in the landslide zone. Hsu et al (2021) pointed out that another possible mechanism related to the interannual variation of terrestrial water storage, rather than the typhoon-associated landslides and erosions.…”
Section: Seismicity In the Landslide Zone In Months Before And After Morakotmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past two decades, a growing number of studies has shown a correlation between meteorological events and earthquake activity in various geological contexts (Costain and Bollinger, 2010). Several sites show the seasonal modulation of the seismicity due to rainfall or snowmelt periods in Japan (Ueda and Kato, 2019); Nepal (Kundu et al, 2017); Taiwan (Hsu et al, 2021); Oregon, USA (Saar and Manga, 2003); California, USA (Johnson et al, 2017;Montgomery-Brown et al, 2019); and Italy (D'Agostino et al, 2018). Other observations display a punctual increase of seismic activity following an exceptional rainfall episode, for example in the Swiss Alps (Roth et al, 1992), German Alps (Kraft et al, 2006), and southern France (Rigo et al, 2008).…”
mentioning
confidence: 99%